Co-assembled and microfabricated bioactive membranes - Mendes, A. C. (2013)
The fabrication of hierarchical and bioactive self-supporting membranes, which integrate physical and biomolecular elements, using a single-step process that combines molecular self-assembly with soft lithography is reported. A positively charged multidomain peptide (with or without the cell-adhesive sequence arginine-glycine-aspartic acid-serine (RGDS)) self-assembles with hyaluronic acid (HA), an anionic biopolymer. Optimization of the assembling conditions enables the realization of membranes with well-controlled and easily tunable features at multiple size scales including peptide sequence, building-block co-assembly, membrane thickness, bioactive epitope availability, and topographical pattern morphology. Membrane structure, morphology, and bioactivity are investigated according to temperature, assembly time, and variations in the experimental setup. Furthermore, to evaluate the physical and biomolecular signaling of the self-assembled microfabricated membranes, rat mesenchymal stem cells are cultured on membranes exhibiting various densities of RGDS and different topographical patterns. Cell adhesion, spreading, and morphology are significantly affected by the surface topographical patterns and the different concentrations of RGDS. The versatility of the combined bottom-up and top-down fabrication processes described may permit the development of hierarchical macrostructures with precise biomolecular and physical properties and the opportunity to fine tune them with spatiotemporal control.